Objects - Zaidi, Rehan (JavaScript Essentials for SAP ABAP Developers, 2017)
In JavaScript, an object is an unordered list of properties. A property is composed of a name and a value and can also be a function. In this case, the function is called a method. This chapter covers some of the standard objects you need to be familiar with when coding with JavaScript. It also presents examples of their properties and the methods you are most likely to use with them. The chapter also covers arrays, Boolean objects, string objects, and date objects.